Continuous subcutaneous insulin infusion: Special needs for children. Issue 4 (20th April 2017) - Adolfsson, Peter; Ziegler, Ralph; Hanas, Ragnar
Abstract : Continuous subcutaneous insulin infusion (CSII) is a very common therapy for children with type 1 diabetes. Due to physiological differences they have other requirements for their insulin pump than adults. The main difference is the need for very low basal rates. Even though most available insulin pumps reach a high accuracy at usual basal rates, accuracy decreases for lower rates. In addition, the lowest delivered amount at 1 time is limiting the fine tuning of the basal rate as well as the option for temporary basal rates. Alarms in case of occlusions depend on accumulation of a certain amount of insulin in the catheter, and therefore the time until such an alarm is triggered is much longer with lower basal rates. Accordingly, the risk for hyperglycemia developing into diabetic ketoacidosis increases. The availability of bolus advisors facilitates the calculation of meal and correction boluses for children and their parents. However, there are some differences between the calculators, and the settings that the calculation is based on are very important. Better connectivity, for example with a system for continuous glucose monitoring, might help to further increase safety in the use of CSII in children. When selecting an insulin pump for a child, the features and characteristics of available pumps should be properly compared to ensure an effective and safe therapy.